Kuliah Kerja Nyata Tematik Domisili: Sebuah Program Alternatif Pengabdian Masyarakat di Masa Pandemi Covid-19 - Eko Sri Wiyono; Dea Amanda Noventri; Deca Febriantika; Dina Putri Dermawan; Arcahya Dinda Kasihannisa; Sekar Ayu Khairunnisa; Melianti Melianti; Akhmad Muhriz Haqiqi; Karina Rachma Suryani; Shafira Nur Sadrina; Santi Sejati; Khoirunnisa Rizki Dwi Jayati; Shella Putri Intan Sabak Aji; Fadmiar Nibras Assilmi; Koharudin Koharudin; Juni Viona Nurayuni; Shandathyana Nisabillah; Shella Shella; Deni Pebriansyah; Nurhidayat Nurhidayat; Alfi Alfi (Institut Pertanian Bogor, 2022)
The Thematic Community Service Program Domicile (KKNT) is a community service activity carried out in June–August 2021 in anticipation of the Covid-19 pandemic. This activity program is carried out using an online media approach and blended learning (a combination of online and field trips) to comply with health protocols according to circulars that have been set by the government. Several planned activities have been successfully implemented. With its various advantages and disadvantages, the KKNT has provided suitable lessons for implementing The Thematic Community Service Program Domicile. The results of the evaluation with a comparative descriptive approach starting from the planning process and implementing activities show that the implementation of the Thematic Community Service Program Domicile in the Covid-19 pandemic condition is still possible to be carried out by taking into account the readiness of several things, such as communication technology, information technology capabilities owned by students and partners, awareness of partners, and the ability of The Thematic Community Service Program Domicile students in compiling training/counseling content.